Pre-Hispanic Periods and Diet Analysis of the Inhabitants of the Quito Plateau (Ecuador): A Review - Roberto Ordoñez-Araque; Jenny Ruales; Paul Vargas-Jentzsch; Luis Ramos-Guerrero; Martha Romero-Bastidas; Carlos Montalvo-Puente; Sthefano Serrano-Ayala (MDPI AG, 2022)
In all of the different historical periods during its development, the pre-Hispanic inhabitants of the Quito plateau and its valleys used the flora and fauna for food and the development of their society. The objective of this study is to review the chronological periods that correspond to the territory of the current city of Quito, as well as the possible diet, and the toxic substances to which the inhabitants could be exposed. The main archeological sites in the territory of Quito are as follows: (1) 11000–1500 BC (Preceramic): El Inga-Rancho Bajo; (2) 1500–500 BC (Formative): Rancho Bajo-Cotocollao-Tajamar; (3) 500 BC–500 AD (Regional Development): Jardín del Este; (4) 500–1500 AD (Integration): La Florida–Rumipamba-Chillogallo-Chilibulu and; (5) 1500–1534 AD (Inca period): Quito, which is today’s historic center and urban area. The probable main vegetable foods that were consumed were corn, potato, quinoa, beans, chili, and oca, while the main meat foods were rabbit, guinea pig, deer, guanta, and llama. The possible toxic substances to which the inhabitants could be exposed by consuming contaminated foods were glycoalkaloids (α-solanine and α-chaconine), tropane alkaloids, and heavy metals. The analysis of biomolecules in archeological remains is feasible, and some physicochemical analytical techniques are capable of using small samples. Moreover, the possible application of spectroscopic methods, supported by quantum chemistry, in order to predict the occurrence of molecules in the past cannot be ruled out.